Early exposure to added sugars via infant formula may explain high intakes of added sugars during complementary feeding beyond maternal modeling - Griebel-Thompson, Adrianne K.; Fazzino, Tera L.; Cramer, Emily; Paluch, Rocco A.; Morris, Katherine S.; Kong, Kai Ling (Frontiers in Nutrition, 2023)
Background: Research has shown that early exposure to added sugars from table food is related to increased intake of added sugars in later childhood. The earliest window of exposure to added sugars may be in infancy via infant formula. However, beyond the well-established factors of maternal lifestyle and modeling, there is a lack of research examining how exposure to added sugars from infant formula influences infant/toddler added sugar intakes from table foods and sugar sweetened beverages (SSB).Objective While accounting factors previously associated with infant/toddler added sugar intakes and maternal SSB consumption (proximal measure of maternal modeling), this study aims to examine if there is an association between added sugars in infant formula and added sugar intakes from table foods and SSB during the complementary feeding period.Methods: This is a secondary, cross-sectional analysis using three-day caregiver-reported 24-hr dietary recalls in a cohort of infant/toddlers (n= 95), ages 9-<16 mos., enrolled in a music intervention trial. Hierarchical stepwise regression was used to estimate the association between exposure to added sugars from infant formula and 1) intake of added sugars from table food and 2) SSB consumption. Infant/toddler SSB consumption was transformed to account for distributional properties. We performed incremental F-tests to determine whether the addition of each step improved model fit (R 2 ).Results: Early exposure to added sugars via infant formula was associated with infant/toddler SSB (ΔR 2 =0.044, Finc(1, 87) =6.009, p =0.016) beyond sociodemographic and maternal SSB consumption, but not with infant/toddler added sugar intakes from table foods (ΔR 2 =0.02, Finc(1, 87) =3.308, p=0.072). Conclusion: While past studies have identified circumstantial (i.e., sociodemographic), or indirect (i.e., maternal lifestyle and modeling), mechanisms contributing to higher infant/toddler added sugar intakes, this study identifies exposure to added sugars from infant formula as a possible direct mechanism explaining why some infants/toddlers consume more added sugars.